ClassSearch: Facilitating the Development of Web Search Skills through Social Learning - Moraveji, Neema; Morris, Meredith Ringel; Morris, Dan; Czerwinski, Mary; Henry Riche, Nathalie (CHI '11 Proceedings of the SIGCHI Conference on Human Factors in Computing Systems, 2011)
We explore the use of social learning – improving knowledge skills by observing peer behavior – in the domain of Web search skill acquisition, focusing specifically on co-located classroom scenarios. Through a series of interviews, pilot studies, and classroom deployments, we conclude that a peripheral display of Web search activity within a classroom facilitates both social learning and teacher-led discourse. We present the ClassSearch system for shared awareness of Web search activity, which embodies principles gleaned from our iterative design process, and show results from a ClassSearch deployment in twelve middle-school classroom sessions. Finally, we highlight design suggestions and opportunities for future work while taxonomizing the space of co-located search pedagogies.
Best Paper Nominee